Розв’язати рівняння: (2х-3)(2х+3)=4х(х+1)-1

арина1382 арина1382    1   30.05.2023 23:34    0

Ответы
vladsmolin4554 vladsmolin4554  30.05.2023 23:35

х = -2

Пошаговое объяснение:

(2х - 3)(2х + 3) = 4х(х + 1) - 1

4х² - 9 = 4х² + 4х - 1

-9 = 4х - 1

-4х = -1 + 9

-4х = 8

х = 8 ÷ (-4)

х = -2

ПОКАЗАТЬ ОТВЕТЫ
Zipchik Zipchik  30.05.2023 23:35

-2

Пошаговое объяснение:

(2х - 3)(2х + 3) = 4х(х + 1) - 1

4х² + 6х - 6х - 9 = 4х² + 4х - 1

4х² - 9 = 4х² + 4х - 1

-9 = 4х - 1

-4х = -1 + 9

-4х = 8

х = 8 : (-4)

х = -2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика